2005
DOI: 10.1111/j.1538-7836.2005.01138.x
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Protein S mRNA synthesis in human liver and various cell lines

Abstract: It appears likely that, rather than a possible founder effect, the Bb 14 Arg fi Cys mutation occurs in a CpG dinucleotide (CGT to TGT change) which is a recognized mutation hot spot.Among all the dysfibrinogen variants so far reported, only Bb 14 Arg fi Cys and Aa 554 Arg fi Cys mutations show a sufficient number of reports to suggest an association with increased risk of thrombosis (http://www.geht.org/databaseang/fibrinogen/). Despite the fact that the pathophysiology still remains obscure, the presence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The different construct sizes in both studies could cause the different effects of the mutations. As described above, Tatewaki et al (33) used a construct that ranged from Ϫ282 to Ϫ161, thereby lacking several of the previously identified transcription start sites (32), whereas the construct used in this report is larger, spanning nucleotides Ϫ370 to Ϫ1 in relation to the PROS1 translational start codon. Co-transfection of HepG2 cells with FOXA2 and PS370-luc or the PS370-luc FOXA2 mutant resulted in a slight induction of the wild type PS370-luc but not of the FOXA2 mutant construct.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The different construct sizes in both studies could cause the different effects of the mutations. As described above, Tatewaki et al (33) used a construct that ranged from Ϫ282 to Ϫ161, thereby lacking several of the previously identified transcription start sites (32), whereas the construct used in this report is larger, spanning nucleotides Ϫ370 to Ϫ1 in relation to the PROS1 translational start codon. Co-transfection of HepG2 cells with FOXA2 and PS370-luc or the PS370-luc FOXA2 mutant resulted in a slight induction of the wild type PS370-luc but not of the FOXA2 mutant construct.…”
Section: Discussionmentioning
confidence: 99%
“…EMSA buffers were purchased from Active Motif (Carlsbad, CA) and used according to the manufacturer's recommendations. Double-stranded oligonucleotides were end-labeled using [␥- 32 P]ATP and T4 polynucleotide kinase. The position numbers for the oligonucleotides in Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter and first exon are absent from the PROS2 gene, and the promoter region of PROS1 has been poorly investigated in contrast to the coding regions. It has been reported that transcription from the PROS1 promoter is directed from multiple start sites and that the PROS1 5Ј-flanking region lacks the characteristic "CAAT" and "TATA" boxes (23).…”
Section: Protein S (Ps)mentioning
confidence: 99%
“…Transcription from the PROS1 promoter is directed from multiple start sites (de Wolf et al , 2005), and recently two groups have characterised essential regulatory elements in the 5′‐flanking region of the PROS1 (Tatewaki et al , 2003; de Wolf et al , 2006). Various transcription factor binding sites were identified within the first 400‐bp proximal to the PROS1 translational start site, including multiple binding sites for ubiquitous transcription factors Sp1 and Sp3.…”
mentioning
confidence: 99%